The Genome of Winter Moth (Operophtera brumata) Provides a Genomic Perspective on Sexual Dimorphism and Phenology - Derks, Martijn F.L. (Genome Biol Evol, 2015)
The winter moth (Operophtera brumata) belongs to one of the most species-rich families in Lepidoptera, the Geometridae (approximately 23,000 species). This family is of great economic importance as most species are herbivorous and capable of defoliating trees. Genome assembly of the winter moth allows the study of genes and gene families, such as the cytochrome P450 gene family, which is known to be vital in plant secondary metabolite detoxification and host-plant selection. It also enables exploration of the genomic basis for female brachyptery (wing reduction), a feature of sexual dimorphism in winter moth, and for seasonal timing, a trait extensively studied in this species. Here we present a reference genome for the winter moth, the first geometrid and largest sequenced Lepidopteran genome to date (638 Mb) including a set of 16,912 predicted protein-coding genes. This allowed us to assess the dynamics of evolution on a genome-wide scale using the P450 gene family. We also identified an expanded gene family potentially linked to female brachyptery, and annotated the genes involved in the circadian clock mechanism as main candidates for involvement in seasonal timing. The genome will contribute to Lepidopteran genomic resources and comparative genomics. In addition, the genome enhances our ability to understand the genetic and molecular basis of insect seasonal timing and thereby provides a reference for future evolutionary and population studies on the winter moth.